Ambiguity Attitudes and Surprises: Experimental Evidence on Communicating New Information within a Large Population Sample - Aljoscha Minnich; Hauke Roggenkamp; Andreas Lange (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper investigates ambiguity attitudes for natural events (temperatures) and how they are updated following new information. Using a general population sample, we first obtain baseline ambiguity attitudes for future weather events based on real temperatures over several past days. Second, we study the influence of different communication types on updating the ambiguity attitudes: participants are given either point estimators, interval estimators, or the combination of both as weather forecasts. We further vary whether the forecast is surprising or in line with the initially received information. In contrast to claims that ambiguity aversion may increase in response to surprising news, we find that ambiguity attitudes are rather robust to new information and variants of their communication. Yet, different variants of communicating new information significantly change the belief updating process and affect the matching probabilities given to specific events. Our sample allows us to analyze sociodemographic correlates of ambiguity attitudes and the updating of ambiguity attitudes to new information.
Keywords: D81; D83; C93; 330; ambiguity attitude; belief updating; expert forecasts; survey experiment